2018
DOI: 10.1002/cctc.201800598
|View full text |Cite
|
Sign up to set email alerts
|

Template‐free Scalable Synthesis of Flower‐like Co3‐xMnxO4 Spinel Catalysts for Toluene Oxidation

Abstract: The rational design of low-cost transition metal catalysts that exhibit high activity and selectivity may be the most significantly investigated in heterogeneous catalysis. In this study, Co 3-x Mn x O 4 (x = 0.75, 1.0, and 1.5) mixed metal oxides were successfully synthesized by a controlled template-free autoclave strategy and studied for toluene oxidation. It is found that the Co-rich sample showed markedly enhanced activity and the 3D dandelion-like Co 2.25 Mn 0.75 O 4 catalyst exhibited in the highest tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(38 citation statements)
references
References 31 publications
(35 reference statements)
0
35
0
Order By: Relevance
“…Oxides designed for hierarchical hollow nanostructures with a large surface-to-volume ratio and interconnected pathways for both electrons and ions are of great significance for catalytic oxidation [14][15][16]. Wang reported template-free scalable synthesis of flower-like Co 3−x Mn x O 4 spinel catalysts for toluene oxidation due to rich surface oxygen species over a 3D flower-like structure [17]. Templating-engaged methods employing chemical etching are considered a facile approach, forming hollow structures through the controlled assembly of the desired shells on templates [18].…”
Section: Introductionmentioning
confidence: 99%
“…Oxides designed for hierarchical hollow nanostructures with a large surface-to-volume ratio and interconnected pathways for both electrons and ions are of great significance for catalytic oxidation [14][15][16]. Wang reported template-free scalable synthesis of flower-like Co 3−x Mn x O 4 spinel catalysts for toluene oxidation due to rich surface oxygen species over a 3D flower-like structure [17]. Templating-engaged methods employing chemical etching are considered a facile approach, forming hollow structures through the controlled assembly of the desired shells on templates [18].…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] Additionally, extensive efforts have revealed that the synergistic effect of Co species and other transition metal oxides has dramatically enhanced the redox properties and catalytic activities due to the formation of a solid solution, compared with single oxides. 11,[28][29][30][31] For example, Jiang et al 30 reported the preparation of Mn-Co-O x nanocubes with different Mn/Co molar ratios derived from metal-organic frameworks. It is shown that hierarchical Mn-Co-O x mixed metal oxides exhibited the better redox properties, more exposed active sites and superior oxidation performances of total toluene oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study discovered that Co 3 O 4 catalysts with different morphologies (rods, sheets, plates, cubes, belts and spheres, etc .) exhibit different catalytic properties ,. For instance, Hu et al.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Tricobalt tetraoxide (Co 3 O 4 ), one of the most promising materials, has been used in catalytic oxidation, lithium-ion batteries as energy storage materials, sensor devices and other important fields. [24][25][26][27][28] A number of studies have focused on Co 3 O 4 for the catalytic oxidation of VOCs due to its high catalytic activity, low cost and environmental benignity. A number of references show that the morphology of a catalyst can greatly affect its catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation